THE USE OF BIO-MOLECULAR SUBSTANCE OF MARINE BIOTA AS AN ALTERNATIVE EARLY INDICATOR OF OIL POLLUTED ENVIRONMENT: A NEW APPROACH FOR MONITORING CONSIDERATION - M.S. Wibisono (Scientific Contributions Oil and Gas, 2005)
Oil enters the marine environment from various sources, for example from the accidental and intentional release of petroleum wastes during the production, transportation, refining and the use of this fossil fuel, domestic/industrial oily waste discharge and others. Oil from tanker spills, which is considered to occur rarely, usually only affects the coastal environment if prevailing winds and currents are directed onshore. The presence of stranded tar-balls on beaches has been reported in some areas due to the tanker routes nearby. A report of Lemigas and CNEXO (1984) showed that several sandy beaches on islands in the vicinity of Malacca Strait (Riau Islands), Makassar Strait (Langa beach) and in Kepulauan Seribu (Pulau Pari and Pulau Tikus) were polluted by stranded tarballs by as much as 7.8-67 g/ m (net weight) from 1982 survey and between 4.8- 494 g/m from the 1984 survey. This report indicated that the heavy range of oil pollution increased from 1982 to 1984. Results of laboratory analysis on tar samples using gas chromatography indicated that four different types of oil were present viz.: crude oil residue, tanker sludge residue, fuel oil residue and weathered crude oil residue. Unfortunately, no similar data are available after the 1984 survey even the current oil pollution has occurred in the vicinity of Pulau Pabelokan and Pulau Pramuka in 2004. Although oil pollution from refinery run-off has been estimated to be smaller compared to accidental tanker spills, such run-off will directly affect the coastal environment if the effluent is not managed properly. These industrial and refinery effluents, which usually flow into the coastal zone, result in relatively low levels of pollution for a long period of time. As a consequence the delayed effects of such pollution will occur. In this case marine organisms might be affected or stressed physiologically rather than killed under such a regime. Furthermore, increasing activities of processing units of a refinery from Atmospheric Residue Hydro Demetalisation (ARHDM) and from Residue Fluid Catalytic Cracking (RFCC) may result the increasing discharge in a significant number of volume. The discharge volume of liquid wastes and its quality depend on the quantity and type of crude as a feed stock. If the feed stock derived from naphtenic oils or heavy oils or high sulphur oils, care should be taken to the water disposal for the sake of environmental protection. In monitoring activities for the refinery effluent, the standard has been renewed since 1996 by the Ministerial Decree of the Minister of Environment No. 42/MENLH/10/1996 in the Appendix IV and Appendix V. Although the available treatment plant system is being used satisfactorily, but in some cases, several parameters including hydrocarbon contents still exceed the standard quality of the above Ministerial Decree. On the other hand, oil and grease contents as one of the parameters from the receiving bodies that should be analyzed have been designated, as stated in the Government Regulation No. 82/2001 and in the Ministerial Decree of Minister Environment No. 51/ 2004 , instead of petroleum hydrocarbons. But from the basic scientific point of view, the oil and grease contents have the different meaning from the petroleum hydrocarbon contents in terms of chemical formula and its impacts on the aquatic biota. Oil and grease contents include the expression of the oils derived from biological products such as the fatty acids from aquatic organisms, palm oils and others. Unlike in the petroleum hydrocarbons, in plant oils/oil and grease no toxic compounds are found in its HC chains viz.: vanadium, nickel, phenols, sulphide, aromatics, mercaptans, etc. Since the impacts of petroleum hydrocarbons to the aquatic animals are not able to compare to those impacts of plant oils/oil and grease even at the same concentration, so that the oil and grease content seem to be in-significant and irrelevant to the petroleum activities. Total petroleum hydrocarbon contents in water and poly aromatic contents (= naphthalene, phenanthrene, dibenzthiophene and its alkylated homologues) are more significant than oil and grease. The aquatic (marine) biota such as bivalves can take up oil into their tissues, which is at low concentration in the water (Blumer et al., 1970) by ingestion. Ingestion of hydrocarbons causes cell tissues to become stressed and undergo a series of often ir-reversible biochemical and cellular changes. The changes manifest themselves as alterations in the animal physiology and therefore rep- resent good indicator of xenobiotic bio-accumulation (Moore and Lowe, 1985). The characteristic cellular defence mechanisms in all organisms studied to date under environmental stress involves the induction of certain biomolecular substance which constitutes protein compounds which Atkinson and Walden (1985) called as heat shock proteins (hsp) or stress proteins (sp) . It is evident that synthesis of families of proteins of 60 kDa (kilo Dalton) and 70 kDa molecular weight (hsp 60 and hsp 70) and other stress proteins by cells of all organisms occurs in response to a wide variety of envi- ronmental stressors e.g. elevated temperatures, heavy metals, thiol reactive agents and amino acid analogues (Lindquist, 1986; Mizzen et al; 1989; Sanders, 1990). At least 30 stress proteins have been identified by gel electrophoresis (Anderson, 1989), and mainly they have molecular weights between 22 to I110 kDa (Schlesinger et al., 1982). Hsp 90, hsp 70 and hsp 60 are predominant in all prokaryotes and eukaryotes. A group of low mo- lecular weight proteins (hsp 20 - 30) is also commonly found as shown by Burdon (1987). Since bivalve mollusks are sessile, plentiful, inexpensive and relatively easy to maintain in the laboratory, their use is becoming important in monitoring programs and toxicological studies. Compared to mollusks, fish are expensive and prone to secondary stresses (such as handling and infection by fungi and bacteria) and they can avoid the polluted area. Many coastal areas in Indonesia produce several kinds of commercially valuable shellfish such as cupped oysters (Crassostrea sp.), scallops (Pecten spp), blood cockles (Anadara granosa, L), clam (Tridacna spp.) and green mussels (Mytillus viridis, L). Unfortunately there is little information on the use of these species as bio-indicators of oil pollution, particularly with respect to bio-molecular substance examination as a tool for monitoring activities. Electrophoresis is usually implemented for the examination of glycoproteins, phosphoproteins, enzymes, etc. It sems that the use of biological substance through electrophoresis method in oil pollution monitoring is a "new" break-through that needs to be considered. The aim of the study was to propose an alternative method in environmental monitoring particularly at sub lethal effects through the use of bio-molecular of suitable shellfish in Indonesia as bio-indicator of oil pollution. The examination of the substance can be carried out by Onedimensional SDS - PAGE (Sodium Dodecyl Sulphate – Poly acrylamide Gel Electrophoresis) method